A speech act study of online comments towards covid-19 report in the Malaysian National Security Council's official Facebook page / Nor Hairunnisa Mohammad Nor and Nor Syamimi Iliani Che Hassan - Mohammad Nor, Nor Hairunnisa; Che Hassan, Nor Syamimi Iliani (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
The COVID-19 pandemic has adversely affected the world, crippling its economies, impacting the education system, and debilitating emotions and mental health. However, with the emergence of new virus mutations, Malaysia has yet to win the battle against this wave of COVID-19. This has led to diverse reactions among its citizens. We observe that many Malaysians are now flooding their social media platforms to vent their frustration or even blame various parties for this COVID-19 spike in the country. Hence, this study was designed to investigate the speech acts employed by Malaysian Facebook users in constructing their online comments amid the COVID-19 crisis. The study corpus consisted of 555 Facebook comments to daily reports of COVID-19 cases published on the Facebook page of the Malaysian National Security Council in July and August 2021. The entire data was coded using ATLAS.ti version 22. Based on the findings, we discovered that the most frequently constructed speech acts in this study corpus were assertive, followed by expressive and directive, which were addressed to two target recipients: the government and the public. The analysis of this study would enable us to understand the various ways language is used in computer-mediated communication, particularly the types of speech acts used in social media such as Facebook.